User Experience Analysis: ChatGPT-based AI in Islamic Religious Education Learning - Nisa, Wahdatun; Sulaiman, Mashithah (CV Sinergi Ilmu dan Publikasi, 2025)
The purpose of the study was to analyse the user experience of ChatGPT-based AI in Islamic education learning. This study used a quantitative approach with a survey research type, with 84 teachers in Teacher Professional Education (PPG) as the respondents. The instrument had twenty-six items and six scales and was analysed using ueq-online.org. The study's findings demonstrated the value of incorporating AI under the direction of experienced educators in the subject of Islamic religious studies, on the six scales of user experience: Attractiveness, Efficiency, Perspicuity, Dependability, Stimulation, and Novelty, found on the benchmark above average, except on the Stimulation scale the results were good, meaning that the Stimulation value has shown more attention for Islamic Education teachers, In conclusion, even if the study's findings are outstanding, it is crucial to apply ChatGPT-based AI in Islamic education by taking consideration of students' interests, difficulties, and other barriers to make learning more innovative and effective.